2015
DOI: 10.1016/j.jppr.2015.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Effects of viscous dissipation and slip velocity on two-dimensional and axisymmetric squeezing flow of Cu-water and Cu-kerosene nanofluids

Abstract: Squeezing flow of nanofluids has been taken into account under the effects of viscous dissipation and velocity slip. Two types of base fluids are used to study the behavior of Copper nanoparticles between parallel plates. Nonlinear ordinary differential equations governing the flow are obtained by imposing similarity transformations on conservation laws. Resulting equations are solved by using an efficient analytical technique the variation of parameters method (VPM). Influences of nanoparticle concentration a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
25
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

4
6

Authors

Journals

citations
Cited by 65 publications
(28 citation statements)
references
References 43 publications
3
25
0
Order By: Relevance
“…(9) and (10) with the associated boundary conditions (11) using VPM [40][41][42][43][44][45] the velocity and temperature can be written as,…”
Section: Solution Using Vpmmentioning
confidence: 99%
“…(9) and (10) with the associated boundary conditions (11) using VPM [40][41][42][43][44][45] the velocity and temperature can be written as,…”
Section: Solution Using Vpmmentioning
confidence: 99%
“…They considered the concentric annulus between cold and heated elliptic cylinders by applying magnetic action. Many researchers added valuable information about this novel field of nanofluids [18][19][20][21][22][23][24][25][26][27] The present study deals with the three dimensional model of heat flow of a nanofluid in a rotating system under the action of magnetic forces. Detailed analysis of the effects of Reynolds number, magnetic parameter, Rotation parameter, Diffusive parameter, Thermophoretic and Brownian motion parameters on the velocity, temperature, concentration profiles and rate of heat transfer is provided.…”
Section: Introductionmentioning
confidence: 99%
“…They also extended these studies to the case of nanofluids. One can easily find enough literature on convective nano fluid flows, however some of the studies are reported in [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] and references therein. Those also include some studies on nanofluid flow over a permeable stretching sheet saturated by porous medium.…”
Section: Introductionmentioning
confidence: 99%